Dissociation in patients with non-affective psychosis: prevalence, symptom associations, and maintenance factors - Cernis, E; Molodynski, A; Ehlers, A; Freeman, D (Elsevier, 2021)
Dissociation is problematic in its own right for patients with psychosis but may also contribute to the occurrence of psychotic experiences. We therefore set out to estimate in a large cohort of patients with psychosis the prevalence of dissociative experiences, and assess using network models the relationships between dissociation, its potential maintenance mechanisms, and mental health symptoms.